Wacana “Investigative Reporting” - Septiawan Santana Kurnia (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2006)
Investigative reporting, as the result of recent journalism development, becomes a new benchmark in journalism practice. To learn more about investigative journalism, one can learn from Ida Tarbell, a legend of investigative journalism, and his works. Tarbell began his journalism practice by doing preliminary research over hundreds of documents. This phase was called paper trail. Tarbell used combination of data gathering methods to gaining in depth and perspective on his issue. In order to enliven his story, Tarbell utilized narrative technique to tell his story. In recent times, Tarbell reportage become a model of basic investigative journalism. As pointed out in this article, data was dig through a series of phases: (1) surface facts; (2) repertorial enterprise; dan (3) interpretation and analysis. Based on this basic procedures, Paul N. Williams described 11 steps of investigative reporting, started from conception to publication and follow-up stories. The key of success in writing investigative reporting is probing and digging, attentively, intensively.